2011
DOI: 10.1024/1422-4917/a000113
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathologische und komorbide Störungen inhaftierter Jugendlicher in Österreich

Abstract: Considering that juvenile detainees are burdened by high rates of psychopathology and comorbidity, it is essential to develop a substantiated diagnostic procedure in order when making treatment decisions; different disorder patterns must be considered in conjunction with detained juveniles. The patterns of psychopathology observed might be related to different characteristics in the development of delinquent behavior, in treatment needs, and legal prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
1
6
0
6
Order By: Relevance
“…The high proportion of perpetrators with psychiatric diagnoses found in our sample is in line with comparable studies that found psychiatric diagnoses in 90% of prisoners in young offenders' institutions (17,18).…”
Section: Discussionsupporting
confidence: 92%
“…The high proportion of perpetrators with psychiatric diagnoses found in our sample is in line with comparable studies that found psychiatric diagnoses in 90% of prisoners in young offenders' institutions (17,18).…”
Section: Discussionsupporting
confidence: 92%
“…In einer früheren Studie von Plattner et al (2011), in der inhaftierte Jugendliche in Wien, Österreich, untersucht wurden, wurde für die Darstellung der Überlappung unabhängiger psychischer Störungsbilder das Venn-Polyomino-Diagramm verwendet. Für die Präsentation der Ergebnisse der vorliegenden Studie wurde daher ebenso das Venn-Polyomino-Diagramm eingesetzt.…”
Section: Datenerhebung Und Instrumenteunclassified
“…Wie bereits erwähnt, zeigt die vorliegende Studie, in Übereinstimmung mit anderen Untersuchungen (Colins et al, 2011;Hoeve et al, 2013;McReynolds et al, 2010;Plattner et al, 2011), dass ein hoher Anteil der inhaftierten Jugendlichen unter mehreren gleichzeitig vorliegenden psychischen Störungen leidet. So fanden sich bei 70.5 % zwei, bei 33.6 % drei und bei 12.3 % vier gleichzeitig vorliegende psychische Störungsbilder.…”
Section: Komorbiditätenunclassified
See 1 more Smart Citation
“…Nur in 18 Fällen (15,8%) war dies nicht der Fall. Dieses Ergebnis stimmt überein mit vergleichbaren Studien, die für die Inhaftierten in Jugendstrafanstalten in rund 90% der Fälle zu einer psychiatrischen Diagnose kamen (18,19), gestellt werden konnte. Die hohe Rate an Persönlichkeits-und Verhaltensstörungen in unserer Studie weicht ab von den im Übrigen vergleichbaren Tübinger Studien (15,20,21).…”
Section: Psychische Störungen Und Gewaltdelinquenzunclassified